Sharia Risk Management Strategies for Developing Business in Multinational Companies - Utarindasari, Destiana; Ferdinand, Novingky (International Journal of Sharia Business Management, 2024)
This research aims to analyze sharia risk management strategies implemented by multinational companies in facing global challenges. In the context of international business, companies face various sharia risks that are more complex than local companies, including political, economic, legal and cultural sharia risks. This research uses a qualitative approach with case study methods on several leading multinational companies operating in various industrial sectors. The research results show that multinational companies tend to adopt a proactive approach in identifying, evaluating and managing sharia risks. Cultural factors and local regulations greatly influence the sharia risk management strategies implemented. Companies that successfully integrate a deep understanding of the local environment with global Sharia risk management practices show better performance in dealing with crisis situations. The conclusions of this research suggest that multinational companies need to continuously update and adapt their Sharia risk management strategies to remain resilient in a dynamic business environment